PENGARUH PENYESUAIAN DIRI TERHADAP KECEMASAN KOMUNIKASI INTERPERSONAL PADA REMAJA DI PANTI ASUHAN MUSLIMIN - Aghnia Fathunnisa (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
Abstract The objective of this study is to determine the influence of personal adjustment toward interpersonal communication anxiety in the teenagers of Muslimin Orphanage. The variables in this study were personal adjustment as variable (X) and interpersonal communication anxiety variables as variable (Y). Data analysis technique that is used to test the hypothesis is a simple regression using SPSS version 16.00. Based on calculations, the value of F = 50.207 with a significant value of 0.000. Regression equation Y = 6245 + 0.976X and the influence of personal adjustment toward interpersonal communication anxiety 0.558 (55.8%), which means that personal adjustment affects communication anxiety in adolescent students in an orphanage by 55.8% and the remaining 44.2% is affected by other than personal adjustment. Hence, Ho is rejected and Ha is accepted so it can be concluded that there was a significant effect on personal adjustment toward interpersonal communication anxiety in adolescents in an orphanage. Keywords: Personal adjustment, Interpersonal communication anxiety